A Systematic Review of Complementary Therapy for Treating Osteoarthritis - Ira Purnamasari; Suharyono Suharyono; Suhendra Agung Wibowo (Jurnal Ners, 2020)
Introduction: Osteoarthritis (OA) is a chronic progressive disease that is often experienced by the elderly resulting in pain and joint stiffness which then causes movement or mobility disorders. Complementary therapy eases osteoarthritis with a traditional technique known as non-pharmacological treatment. The aim of this systematic review is to identify the effectiveness of several complementary therapies as osteoarthritis management.Methods: The review was performed according to PRISMA guidelines. We searched from PubMed, Scopus, ProQuest, and ScienceDirect databases. The search identified 14 relevant journals from the 19,123 articles published between 2016 and 2020, and all studies used the Randomized Control Trial (RCT). Results: Complementary therapies consisted of flaxseed poultice compress, acupressure, acupuncture therapy, cumin black oil compress, aromatherapy massage, ginger oil massage, lavender oil massage, sensorimotor exercise, application of heat, exercises with elastic bands, ultrasound therapy, geotherapy combination kinesiotherapy, phonophoresis therapy, and stimulation of compression.Conclusion: The effectiveness of these therapies can be seen from the different results of osteoarthritis patients who received the intervention and the control group. The decrease in the total index WOMAC and Lequesne, VAS and increase in the physical function of patients with osteoarthritis who received the complementary therapy are significantly higher than the control group. It proved that the complementary therapy has positive impact as management of osteoarthritis pain. The effects of complementary therapy have an influence on pain, joint stiffness, and physical function limitations in osteoarthritis patients.